Notices of the Funeral of James, Second Earl of Murray (Proceedings of the Society of Antiquaries of Scotland, 1854)
David Laing discusses the delayed burial of James, second Earl of Moray after his murder in 1592. Various commands were issued to force the Earl's relatives to allow his body to be buried. Laing quotes some of these original documents directly. He also describes an examination of St. Giles' in 1850 that discovered three bodies in a vault, one of which he argues is likely the Earl of Murray. One of Laing's aims in writing this article is to encourage the restoration of the brass monument commemorating the Earl of Murray, which was damaged in alterations to the building in 1829. At the end of the article he notes that the Provost and Magistrates of Edinburgh have agreed to discuss the restoration of the monument.